Experimental model of severe acute pancreatitis in rabbits - Goldenberg,Alberto (2007)
PURPOSE: To develop an experimental model of severe acute pancreatitis in rabbits through a pancreatic ductal injection of sodium taurocholate. METHODS: Twenty-four albino rabbits of the New Zealand lineage were distributed into four groups of six animals (A, B, C and S). The rabbits of three experimental groups (A, B and C) were submitted to a laparatomy and received a pancreatic ductal injection of 1ml/kg sodium taurocholate 5%. Also, they were submitted to further laparatomies after 4h, 8h and 12h, respectively. The control group (S) was subdivided into two groups of three animals: in subgroup S1 only the pancreatic duct catheterization was performed whereas in subgroup S2 the pancreatic duct catheterization as well as an injection of 1ml/kg physiologic solution 0.9% were carried out. After 12 hours, the rabbits were evaluated. In the re-intervention, blood was collected to determine the amylasemia and a pancreatectomy was carried out to investigate interstitial infiltration, steatonecrosis and necrosis of the organ, using an optical microscope. RESULTS: There was an elevation of amylase in all groups thus proving the existence of acute pancreatitis. The size of the interlobular septum increased progressively with a greater variation between group S1 (0.13) and group C (0. 53) (p=0.035). While all the animals in group A exhibited focal cellular necrosis, it was more intense in the rabbits of group B and culminated with a high proportion of severe pancreatic necrosis in group C animals. The difference in the intensity of cellular necrosis showed statistic significance (p=0.001). CONCLUSION: The proposed experimental model demonstrated its reproducibility and effectiveness in producing severe acute pancreatitis in rabbits.